The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.macromol.0c01199
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Continuous and Segmented Nanofibers Containing a π-Conjugated Oligo(p-phenylene ethynylene) Core via “Living” Crystallization-Driven Self-Assembly: Importance of Oligo(p-phenylene ethynylene) Chain Length

Abstract: π-Conjugated nanofibers of controlled length and composition show promising potential applications from biomedicine to optoelectronics. However, efficient preparation of uniform nanofibers from π-conjugated polymers with precise control over length and composition poses an outstanding challenge. Herein, we report the synthesis of a suite of block copolymers (BCPs) containing πconjugated crystalline oligo(p-phenylene ethynylene) (OPE) segments of different chain lengths and a poly(N-isopropylacrylamide) (PNIPAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 100 publications
2
81
1
Order By: Relevance
“…One can note that the length of comicelles increased from 49 nm to 170 nm as the temperature increased from 60 °C to 70 °C (Figures 2B–C, F, S3C−E and Table S1), and then sharply increased from 347 nm to 1216 nm with the increase of temperature from 75 °C to 82 °C (Figures 2D–F, S3F–H and Table S1). The formation of comicelles by co‐self‐seeding tracked the behavior of OPE 9 ‐ b ‐P2VP 56 with a higher resistance toward the heating, [19] which is consistent with the co‐self‐seeding of OPV 5 ‐ and OPV 6 ‐based BCPs [25] …”
Section: Figuresupporting
confidence: 73%
See 3 more Smart Citations
“…One can note that the length of comicelles increased from 49 nm to 170 nm as the temperature increased from 60 °C to 70 °C (Figures 2B–C, F, S3C−E and Table S1), and then sharply increased from 347 nm to 1216 nm with the increase of temperature from 75 °C to 82 °C (Figures 2D–F, S3F–H and Table S1). The formation of comicelles by co‐self‐seeding tracked the behavior of OPE 9 ‐ b ‐P2VP 56 with a higher resistance toward the heating, [19] which is consistent with the co‐self‐seeding of OPV 5 ‐ and OPV 6 ‐based BCPs [25] …”
Section: Figuresupporting
confidence: 73%
“…Living crystallization‐driven self‐assembly (CDSA), including seeded growth and self‐seeding approaches, has emerged as a powerful strategy to generate uniform nanowires of controlled composition and dimension from block copolymers (BCPs) containing a crystalline π‐conjugated segment. However, this strategy is limited to the preparation of nanowires containing a homogeneous π‐conjugated core [14–19] . Recently, Manners and co‐workers [20] reported the preparation of coaxial heterojunction nanowires via a two‐step crystallization strategy.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported since 2011 have involved PLLA, [165][166][167] PE, 168 PFDES, 38 and also hyperbranched poly(ether amine) capped with polyhedral oligomeric silsesquioxane, 143 PCL, 169,170 polycarbonate, 62,171 and π-conjugated polymers such polythiophene, [172][173][174][175] poly(3heptylselenophene), 176 PDHF, 177 oligo(p-phenylenevinylene) (OPV), 178,179 poly(cyclopentenylenevinylene) 180 and oligo(p-phenylene-ethynylene). 181 The use of the living CDSA seeded-growth approach to fabricate well-defined biopolymerbased assemblies has also been reported. Attachment of cyanine dyes to the termini of the DNA segment in DNA-polymer hybrids has been shown to direct self-assembly from spheres to 1D…”
Section: The Living Cdsa Seeded Growth Methodsmentioning
confidence: 99%